P2x7 Receptor Is Essential for Cross-Dressing of Bone Marrow-Derived Dendritic Cells - Garcia Huidobro-Toro, J; Imarai-Bahamonde, C; Acuna-Castillo, C; Valdes-Henriquez, D; Milla-Brito, L; Leiva-Salcedo, D; Robles-Planells, C; Rojo-Castillo, L; Barrera-Ávalos, C (Elsevier Inc., 2021)
T cell activation requires the processing and presentation of antigenic peptides in the context of a major histocompatibility complex (MHC complex). Cross-dressing is a non-conventional antigen presentation mechanism, involving the transfer of preformed peptide/MHC complexes from whole cells, such as apoptotic cells (ACs) to the cell membrane of professional antigen-presenting cells (APCs), such as dendritic cells (DCs). This is an essential mechanism for the induction of immune response against viral antigens, tumors, and graft rejection, which until now has not been clarified. Here we show for first time that the P2X7 receptor (P2X7R) is crucial to induce cross-dressing between ACs and Bone-Marrow DCs (BMDCs). In controlled ex vivo assays, we found that the P2X7R in both ACs and BMDCs is required to induce membrane and fully functional peptide/MHC complex transfer to BMDCs. These findings show that acquisition of ACs-derived preformed antigen/MHC-I complexes by BMDCs requires P2X7R expression. © 2021 The Author(s)